Impactful publications of critical care medicine research in China: A bibliometric analysis - Qiang, Wei; Xiao, Chuan; Li, Zhe; Yang, Li; Shen, Feng; Zeng, Lin; Ma, Penglin (Frontiers in Medicine, 2022)
Background: Although publications have been increasing rapidly, the research quality has yet to improve in the field of critical care medicine (CCM) in China. This study aimed at investigating the current status of and the influential factors for impactful publications in CCM research by Chinese authors. Methods: Publications by authors with affiliation of critical care medicine department or intensive care unit (CCM/ICU) in Chinese as well as American hospitals from 2001 to 2020 were retrieved from Web of Science Core Collection (WoSCC) database for this bibliometric analysis. Moreover, statistical analyses to test factors affecting impactful publications by Chinese authors were performed. Results: Of 13487 articles retrieved by this search strategy, 6622 were published by Chinese authors as first or corresponding author. The annual publications by Chinese authors have been rapidly increasing from 2001 to 2020, and so did the citations to these articles. However, the proportion in the world of publications by Chinese authors was much less than that by American authors each year [M(IQR): 1.85(9.592) vs 27.77(7.3), p<0.001]. In addition, impactful articles were significantly less published by Chinese than by American authors, including articles either in journals with high impact factor (p<0.001) or in the top 10 journals in the field of CCM (5.4% vs 13.4%, p<0.001), and articles with high citation frequence as well (p<0.001). Moreover, the percentage of impactful publications by Chinese authors was likely associated with academic background and regions of the author’s affiliations, funds support, public health event of COVID-19 and collaboration between authors. Conclusion: Our results demonstrated that CCM research in China grew rapidly in recent 20 years. However, the impactful pubications remained limited, largely owing to shortage of comprehensive research training, inactive collaboration and underfunded in CCM research.